Juridical Analysis of the Implementation of Law Number 9 of 1998 on Freedom of Expression in Public (Case Study Period 2020-2025) - Bonari Tua Silalahi; Ismaidar Ismaidar (Journal of Research in Social Science and Humanities, 2026)
This research aims to examine the position and implementation of Law Number 9 of 1998 on Freedom of Expression in Public within Indonesia's national legal system, focusing on the 2020-2025 period as a post-pandemic democratic transition phase. Freedom of expression is a constitutional right guaranteed by the 1945 Constitution, yet violations by law enforcement officers frequently occur in practice. This research employs a normative juridical method with statutory, conceptual, and case approaches. The results indicate that although Law No. 9 of 1998 normatively guarantees citizens' rights to express opinions in public, its implementation during 2020-2025 still faces various challenges. Data from Komnas HAM and YLBHI show an increase in violation cases from 42 cases in 2020 to 67 cases in 2023. Law enforcement officers often act repressively, misinterpret notification procedures, and demonstrate weak supervision of rights violations by authorities. Therefore, legal reform, capacity building for officers, and strengthening of supervisory institutions like Komnas HAM are needed to guarantee constitutional rights.